Kingfisher voyages / Wild weather. - Harris, Caroline, 1964- (London : Kingfisher, 2006)
Describes the science behind several types of weather, including thunderstorms, hurricanes, tornadoes, snow, ice storms, dust storms, and extreme heat, and the effects of each on the earth and human populations. Features color photos and diagrams, foldout pages, and overlays.
Die-cut cover.
Fold-out pages.
Includes index.
Includes index.
Spiral-bound.
Tabbed pages.
Keywords: Storms -- Juvenile literature; Weather -- Juvenile literature; Storms; Weather; Storms; Weather